Antimicrobial susceptibility and serovars of Salmonella from chickens and humans in Ibadan, Nigeria - Kayode Fashae; Folasade Ogunsola; Frank M Aarestrup; Rene S Hendriksen (Journal of Infection in Developing Countries)
Background: This study determines the prevalence and antibiotic resistance of Salmonella serovars from humans and chickens in Ibadan, Nigeria, in 2004-2007.